Five-minute Apgar score and outcomes in neonates of 24–28 weeks' gestation. Issue 4 (15th November 2021) - Shah, Prakesh S; Norman, Mikael; Rusconi, Franca; Kusuda, Satoshi; Reichman, Brian; Battin, Malcolm; Bassler, Dirk; Modi, Neena; Hakansson, Stellan; Yang, Jie; Lee, Shoo K; Helenius, Kjell; et al.
Abstract : Objectives: To assess associations between 5 min Apgar score and mortality and severe neurological injury (SNI) and to report test characteristics in preterm neonates. Design, setting and patients: Retrospective cohort study of neonates 24 0 to 28 6 weeks' gestation born between 2007 and 2016 and admitted to neonatal units in 11 high-income countries. Exposure: 5 min Apgar score. Main outcome measures: In-hospital mortality and SNI defined as grade 3 or 4 periventricular/intraventricular haemorrhage or periventricular leukomalacia. Outcome rates were calculated for each Apgar score and compared after adjustment. The diagnostic characteristics and ORs for each value from 0 versus 1–10 to 0–9 versus 10, with 1-point increments were calculated. Results: Among 92 412 included neonates, as 5 min Apgar score increased from 0 to 10, mortality decreased from 60% to 8%. However, no clear increasing or decreasing pattern was identified for SNI. There was an increase in sensitivity and decrease in specificity for both mortality and SNI associated with increasing scores. The Apgar score alone had an area under the curve of 0.64 for predicting mortality, which increased to 0.73 with the addition of gestational age. Conclusions: In neonates of 24–28 weeks' gestation admitted to neonatal units, higher 5 min Apgar score was associated with lower mortality in a graded manner, while the association with SNI remained relatively constant at all scores. Among survivors, low Apgar scores did not predict SNI. Abstract : In a large multicenter retrospective study of extremely preterm infants, increasing 5-minute Apgar scores were associated with decreasing mortality but low scores did not predict severe neurologic injury in survivors.